Penyesuaian Diri Remaja Awal yang Tinggal di Pondok Pesantren - Fauzia, Wilatus; Devina Rahmadiani, Nixie (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Islam Raden Rahmat Malang, 2023)
Abstrack. Self-adjustment is a process experienced by someone related to environmental demands on individual attitudes, behavior and emotions with the belief that they are capable, adolescents will be encouraged to take advantage of their abilities and be able to develop themselves in their environment. Babby Hasmayni, 2014 (in Ghifani, 2004. This study aims to determine how the adjustment of adolescents living in Pondok pesantren An Nur 1 Putri Bululawang-Malang, besides that this study also aims to determine the factors that influence the process of adjustment behavior of adolescents living in Islamic boarding schools.This study focuses on how the adjustment of adolescents who have just studied at the Pondok Pesantren An Nur 1 Putri Bululawang-Malang who previously studied in ordinary public schools where there are significant differences between characteristics, conditions and environment. 5 factors of adjustment proposed by Schneiders (1964), namely physical condition, personality, education or education, environment, religion and culture. Researchers conducted research at Pondok Pesantren An Nur 1 Putri Bululwang-Malang, to find out the adjustment of teenagers living in Pondo Pesantren An Nur 1 Putri Bululwang-Malang. Data collection techniques were carried out by means of interviews. The data collection tool used is a digital recorder. Analysis of interview data used with non-propablying sampling technique.Based on these several factors, the three subjects have differences in adjusting to Islamic boarding schools, there are internal factors and external factors, namely, the subject has a personality which always follows whatever happens in his life, what he wants to do and what personality type he really dislikes in his life. but he always solves his problems on his own and gets along well. While the subject who has a personality where the subject has been able to be independent and put himself in all situations.Keywords : Adjusment; Adolescent; Boarding Islamic school